2018
DOI: 10.1051/0004-6361/201732067
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the 13CO/C18O abundance ratio towards Galactic young stellar objects and HII regions

Abstract: Aims. Determining molecular abundance ratios is important not only for the study of the Galactic chemistry but also because they are useful to estimate physical parameters in a large variety of interstellar medium environments. The CO is one of the most important molecules to trace the molecular gas in the interstellar medium, and the 13 CO/C 18 O abundance ratio is usually used to estimate molecular masses and densities of regions with moderate to high densities. Nowadays this kind of isotopes ratios are in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…general, the higher values of X 13/18 are located mainly at the borders, or close to them, of regions with ionized gas, where the far-UV photons are likely escaping and selectively photodissociating the C 18 O species as found in previous works (e.g. Areal et al 2018;Kong et al 2015;Shimajiri et al 2014). This is the case of the northeastern region of the UC Hii region, where there are many pixels with high X 13/18 values (about 8), while towards the southwest, in coincidence with a dark cloud, X 13/18 is low (about 3).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…general, the higher values of X 13/18 are located mainly at the borders, or close to them, of regions with ionized gas, where the far-UV photons are likely escaping and selectively photodissociating the C 18 O species as found in previous works (e.g. Areal et al 2018;Kong et al 2015;Shimajiri et al 2014). This is the case of the northeastern region of the UC Hii region, where there are many pixels with high X 13/18 values (about 8), while towards the southwest, in coincidence with a dark cloud, X 13/18 is low (about 3).…”
Section: Discussionsupporting
confidence: 56%
“…This avoids the use of indirect estimations from known elemental abundances, such as the case of the 13 CO/C 18 O abundance ratio (X 13/18 ), that in general it is estimated from a double ratio between the 12 C/ 13 C and 16 O/ 18 O ratios given by Wilson & Rood (1994). In a previous paper (Areal et al 2018), using 12 CO, 13 CO, and C 18 O J=3-2 data we studied the X 13/18 towards a large sample of young stellar objects (YSOs) and Hii regions distributed along the first Galactic quadrant, finding ratios systematically lower than the predicted from the mentioned elemental abundance relations. We also found that the ratios depend not only on the distance to the Galactic center, as shown by Wilson & Rood (1994), but also on the type of source or region observed.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Sect. 5.7, the 13 CO/C 18 O abundance ratio increases in regions of enhanced UV field (Shimajiri et al 2014;Ishii et al 2019;Areal et al 2018). This variation is interpreted in terms of the selective photodissociation and isotopic fractionation (see Bron et al 2018;Fuente et al 2019).…”
Section: Comparison Between Taurus Perseus and Orionmentioning
confidence: 98%
“…To calculate the mass of the sources, we need to take the abundance of C 18 O with respect to H 2 into account. There is a substantial uncertainty in this, which moreover depends on the type of region observed (e.g., PDR regions vs. YSO vs. HII regions), with some authors suggesting lower (Areal et al 2018) or higher (Shimajiri et al 2014) C 18 O versus H 2 abundances that can lead to significantly different results. We adopted the calibration of Frerking et al (1982) for high-density enviroments in ρ Ophiuchus.…”
Section: Gas Temperatures and Column Densitiesmentioning
confidence: 99%